Neurosurgery oral board review - Citow, Jonathan Stuart (Thieme, 2011)
"This book is intended to serve as a supplement to the knowledge gained during the long years of residency and in the early stages of practice. It tried to focus on the major aspects of diseases that a neurosurgeon may encounter, both in clinical practice and on the examination" --Provided by publisher.